Soul surfers forced into a fragmented exteriority - Roslan, Siti Balkish; Ismail, Nor Atiah; Ismail, Sumarni (Faculty of Engineering, Universitas Indonesia, 2025)
This study explores the profound impact of the COVID-19 pandemic on soul surfers, individuals for whom surfing transcends mere sport to embody a spiritual, psychological, and physical communion with the sea and ocean. The pandemic’s restrictions, which limited access to the sea, challenged the core of soul surfing practices, prompting surfers to seek alternative means to sustain their connection with the sea and ocean. Through qualitative research, employing phenomenological analysis, theories of affordance, symbolic interactionism, and interpretive interviews, the study examines the transition from a natural exterior to a built interior, adapting their living spaces to maintain their surfing identity, rituals, practices, and the re-creation of their sacred space that was once the sea and ocean. The study also examines the philosophical implications of identifying as a surfer when physical engagement with the sea is obstructed, highlighting the enduring nature of the soul surfer’s identity beyond the physical act of surfing. The findings reveal a shift towards an inward spiritual and psychological practice, where meditation, mindfulness, and physical training within the confines of their homes served as a bridge to the oceanic experience and a renewed sense of their interior affordances. This adaptation underscores the resilience and creativity of soul surfers in preserving their deeply rooted bond with the sea despite external disruptions. Conclusively, the study offers insights into the dynamic relationship between soul surfers and their sacred spaces, illustrating how the pandemic has reshaped their practices and, by extension, their identities.